Adoption and adaptation of Japanese manufacturing management : a case study of an automotive company in Malaysia - Julia binti Haji Abdul Jabar (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Substantial evidence suggests that practices associated with Japanese Manufacturing Management (JMM) can yield a superior competitive advantage in terms of productivity, quality and provide overall successful business performance. With most of the studies are based on the experience of manufacturing companies in the developed countries, not much attention has been paid to the developing countries. To examine the transfer of the best practice of the JMM locally and obtain the impact of the adoption and adaptation of the JMM, an in-depth case study was conducted in a Malaysian automotive company. This is to identify what are the changes in terms of the philosophy and practices undertaken by the automotive company and ascertain the impact of the JMM on its manufacturing and financial performances. The elements of business performance from the viewpoint of manufacturing based on safety, quality, cost and delivery were quantified and examined. These elements are safety, Parts Per Million (PPM), in-line Defect per Unit (DPU), First Time Quality (FTQ), cycle time, productivity, efficiency and stock level. All elements were quantified since the first year of the adoption and viewed over time to track the trend of achievement. The results show a positive impact to the automotive plant manufacturing performance. For example, safety index has reduced to 0 major accident occurrences. The PPM and In-line DPU have improved by 98% and 91% respectively. The FTQ has improved by 167% and cycle time was reduced from 20 minutes to 6 minutes. The productivity has increased up to 43% whilst the efficiency was at 99.9%. The stock level was reduced from half month to 3 days after the adoption of the JMM. The results of the financial performance also show the profitability of the plant. The revenue has increased up to 92% after the JMM adoption, the percentage of expenses has reduced from 11.04% to 3.06% giving an improvement of 72% whilst the net profit has increased from 5.33% to 8.15%. The Return of Asset (RoA) and Return of Equity (RoE) also show slight improvement despite the effects from the restructuring exercise, tsunami calamity and fluctuation in Japanese exchange rate. In addition, the upward trend for Inventory Turnover Ratio (ITR) during the 3-year period of JMM adaptation had showed that the local company had well managed the inventory level. From this, it can be concluded that the business performance of the automotive plant under study has improved due to the JMM adoption and adaptation.